Seroprevalence of binding and neutralizing antibodies against 18 adeno-associated virus types in patients with neuromuscular disorders - Wang, Xiaoyan; Klann, Patrick Julian; Wiedtke, Ellen; Sano, Yumi; Fischer, Nico; Schiller, Lisa; Elfert, Anna; Güttsches, Anne-Katrin; Weyen, Ute; Grimm, Dirk; Vorgerd, Matthias; Bayer, Wibke (Frontiers in Immunology, 2024)
High levels of pre-existing antibodies are a major challenge for the application of viral vectors since they can severely limit their efficacy. To identify promising candidates among adeno-associated virus (AAV) based vectors for future gene therapies for the treatment of hereditary neuromuscular disorders (NMDs), we investigated the antibody levels in sera from patients with NMDs against 18 AAV types, including 11 AAVs with wild-type capsids, 5 AAVs with peptide-modified capsids and 2 AAVs with shuffled capsids. With regard to the wild-type capsid AAVs, the lowest binding antibody levels were detected against AAV6, AAV5, AAV12 and AAV9, whereas the highest binding antibody levels were detected against AAV10, AAV8, AAV1, and AAV2. The lowest neutralizing antibody levels against wild-type AAVs were detected against AAV12, AAV9, AAV8 and AAV10, and the highest neutralizing antibody levels were detected against AAV13, AAV2 and AAV3. Interestingly, the influence of peptide modifications or shuffling of AAV capsids on antibody binding and AAV neutralization seemed to depend on the parental AAV. While the sex of the serum donors had no significant impact on binding or neutralizing antibody levels, we observed a trend to higher binding antibodies in older serum donors and a clear positive correlation of neutralizing antibody titers with the age of the serum donors. The disease status on the other hand did not have a meaningful impact on antibody levels, with no changes in AAV neutralization. Our data indicate that several wild-type or peptide-modified AAV may be good candidates for therapeutic application due to low pre-existing antibody levels, and that the age of potential recipients rather than their health status with regard to NMDs has the biggest impact on vector applicability.